2010
DOI: 10.1080/14675986.2010.521378
|View full text |Cite
|
Sign up to set email alerts
|

Guiding discussions in the class about ethnic diversity

Abstract: In the literature on intercultural education there is an abundance of text about what ought to be going on in the classroom and a lack of empirical descriptions of the dilemmas of intercultural education in practice. This article describes the practice of five teachers guiding discussions about sensitive issues in ethnically diverse secondary education classes in the Netherlands. On the basis of the literature, we differentiated five requirements regarding the role of teachers in these discussions. With the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…In their research on professionalising in-service teachers to enable them to guide a classroom dialogue on intercultural issues, Radstake and Leeman (2010) point to the importance of the teachers' own critical socio-cultural awareness regarding inclusivity in intercultural teaching, together with their experience of living in ethnic-cultural diversity. This finding corresponds on a theoretical level to the work of Boler and Zembylas (2003), Byram (2014), and Ramaekers (2010), who all stress the importance of reflexivity on the own socio-cultural embeddedness, in addition to a knowledgeoriented and an emotions-focused approach.…”
Section: Teachers' Intercultural Developmentmentioning
confidence: 99%
“…In their research on professionalising in-service teachers to enable them to guide a classroom dialogue on intercultural issues, Radstake and Leeman (2010) point to the importance of the teachers' own critical socio-cultural awareness regarding inclusivity in intercultural teaching, together with their experience of living in ethnic-cultural diversity. This finding corresponds on a theoretical level to the work of Boler and Zembylas (2003), Byram (2014), and Ramaekers (2010), who all stress the importance of reflexivity on the own socio-cultural embeddedness, in addition to a knowledgeoriented and an emotions-focused approach.…”
Section: Teachers' Intercultural Developmentmentioning
confidence: 99%
“…This holds in particular for the normative aspect of citizenship. For example, in a small-scale qualitative study on ethnically diverse classes in the Netherlands, most teachers indicated that they do not feel sufficiently equipped to discuss sensitive topics related to issues of (in)equality and social justice with their students in ethnically mixed classrooms (Radstake and Leeman, 2010). A survey study on citizenship education in England (Oulton et al, 2004) shows that the majority of teachers in both primary and secondary education report not having received formal training to teach controversial issues, with a substantial part indicating that they do not feel well prepared to teach controversial issues.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility exists that the teaching quality in this area is low. This claim corresponds with teachers in diverse classes finding it difficult to discuss controversial issues in class (Radstake and Leeman 2010), or have low self-efficacy in the area of cultural responsiveness (see e.g. Siwatu et al 2016;Tucker et al 2005).…”
Section: Discussionmentioning
confidence: 70%